Factors related to road accidents in Palembang, South Sumatera, Indonesia - Desheila Andarini; Anita Camelia; Mochammad Malik Ibrahim (International Journal of Public Health Science (IJPHS), 2021)
Road traffic injuries are a major public health problem and a leading cause of death and injury worldwide. More than 90% of all road deaths occur in lowand middle-income countries, which own less than half of the world's vehicles. The research aimed was to identify the factors related to road accidents in Palembang, Indonesia. The research method used was qualitative approach by using in-depth interviews and observation. This research was conducted from August to December, 2019. The results showed that the factors related to road accidents were human factor, environmental and climatic factor. From this research, the working areas identified as accidentprone zone were Sukarami II and Ilir Barat I Police Station. Referring to the accident and interviews, it is known that the road locations that have the highest casualties were in the road of Kolonel H. Barlian, Jendral Sudirman, Demang Lebar Daun, Ahmad Yani, and Soekarno Hatta. The conclusion was the accident-prone zone located on the main arterial road in Palembang City, Jendral Sudirman Road with a total of 81 cases of traffic accidents in the last three years that need further investigation to minimize traffic injury.